Study on an optimized grouping RAIM method. Issue 4 (June 2021) - Yan, Qin; Cai, Chenglin; Jia, Wei
Abstract: Receiver Autonomous Integrity Monitoring (RAIM) method is widely used in the field of aviation navigation for its advantages of fast response, low cost and wide coverage. The performance of traditional RAIM is not as good as that of fault detection, and the calculation is complex. With the development of multi-constellation integrated positioning technology, the number of visible satellite is gradually increasing. Although the performance of traditional RAIM method has been improved, but it is not large, and the amount of calculation has increased greatly. In order to solve the above problems, an optimized grouping RAIM method is proposed. Through uniform grouping, fault detection can be directly used to complete fault identification, which reduces a lot of calculation and improves the efficiency and performance. The simulation results of graphics and data show that the algorithm is feasible and effective.